A Pilot Longitudinal Clinical Reasoning Curriculum for Pediatric Residents - James Bowen; Catherine Polak; Joanna Thomson; Lisa Herrmann (Association of American Medical Colleges, 2024)
Introduction Clinical reasoning (CR) is required for physicians. Pediatric residents often gain CR skills through experiential learning. Currently, deliberate education on CR targeted toward pediatric residents is inconsistent. Our objective was to implement a pilot CR curriculum, including five hour-long sessions, and evaluate its impact on self-identified CR Milestones and comfort with CR skills. Methods We used Kern's six steps for curriculum development to develop our curriculum. Five morning report sessions included didactics and small-group activities. Pre/post surveys assessed resident self-identified level on ACGME Milestones related to CR skills (Patient Care 4 [PC4] and Medical Knowledge 2 [MK2]) and comfort with CR skills. The postsurvey assessed resident attitudes toward the sessions. Paired samples for Milestone and comfort-based questions were analyzed using Wilcoxon signed rank tests. Attitude questions were reported with descriptive statistics. Results Each of the five curricular sessions was attended by 40-50 pediatric residents. Seventy-one trainees (58% of residency) and 51 trainees (42% of residency) completed the pre- and postsurveys, respectively, with 20 paired samples. Self-assessment of PC4 (p = .006) and resident comfort with all measured CR skills increased significantly. Of trainees who attended at least one session (n = 44), most reported finding the sessions helpful (97%), relevant to their clinical work (97%), and impactful on their clinical practice (73%). Discussion Following exposure to this CR curriculum, pediatric residents reported increased self-identified competency levels on the evaluated Milestones and improved comfort with CR skills. Dedicated CR education may advance pediatric resident understanding of and comfort with CR.